Relación entre liderazgo y clima laboral en un ambiente organizacional: una revisión aplicada - Leon Manrique, Ana Paula (2023)
work climate. For this purpose, a systematic search of different researches that have related the variables mentioned above was carried out, considering the different professional guidelines established in the PRISMA guide (Urrutia & Bonfill, 2010). The databases consulted were Scopus, ProQuest and Ebsco where 11 researches published between 2018 and 2023 that studied the relationship between leadership and work climate were selected. The results indicated that there is a positive and significant relationship between both variables. In addition, it was identified that the transformational leadership style is the one that has the greatest impact on an adequate climate.